Kreativitas dan Inovasi Terhadap Keberhasilan Usaha Industri Mikro Kecil Menengah (IMKM) di Kota Bogor - Tiara Indah Sari; Dwi Gemina; Erni Yuningsih (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Micro, Small and Medium Industries (IMKM) is a sector that drives the people's economy which often has limitations, including production process technology, competition for similar businesses and the difficulty of accessing capital, which are obstacles faced by Bogor City IMKM business actors. This research aims to determine the influence of creativity and innovation on business success. The sample from this research consisted of 50 respondents using a purposive sampling technique, namely a technique for determining samples with certain considerations. The results of this research show that Creativity and Innovation simultaneously have a positive and significant effect on business success. The same shows that the R Square is 50.1%, while the remaining 49.9% is influenced by other factors not included in this research. Meanwhile, partially creativity and innovation have a positive and significant effect on business success.